The glutaminase (CgGLS-1) mediates anti-bacterial immunity by prompting cytokine synthesis and hemocyte apoptosis in Pacific oyster Crassostrea gigas - Yage Liang; Meijia Li; Zhaoqun Liu; Yuanmei Li; Lingling Wang; Linsheng Song (Scientific Reports, 2021)
Abstract Glutaminase, an amidohydrolase enzyme that hydrolyzes glutamine to glutamate, plays crucial roles in various immunomodulatory processes such as cell apoptosis, proliferation, migration, and secretion of cytokines. In the present study, a glutaminase homologue (designated as CgGLS-1) was identified from Pacific oyster Crassostrea gigas, whose open reading frame was of 1836 bp. CgGLS-1 exhibited high sequence identity with vertebrate kidney-type GLS, and closely clustered with their homologues from mollusc C. virginica. The enzyme activity of recombinant CgGLS-1 protein (rCgGLS-1) was estimated to be 1.705 U/mg. CgGLS-1 mRNA was constitutively expressed in all the tested tissues of oysters, with the highest expression level in hemocytes. CgGLS-1 mRNA expression in hemocytes was significantly up-regulated and peaked at 6 h (2.07-fold, p < 0.01) after lipopolysaccharide (LPS) stimulation. The CgGLS-1 protein was mainly distributed in the cytoplasm with a significant co-location with mitochondria in oyster hemocytes. The content of Glu in the oyster serum was significantly decreased after the inhibition of CgGLS-1 using specific inhibitor Bis-2- [5-(phenyl acetamido)-1,3,4-thiadiazol-2-yl] ethyl sulfide (BPTES), and the expression levels of CgmGluR6, CgAP-1, cytokines CgIL17-5 and CgTNF-1 were significantly decreased after BPTES and LPS stimulation. The transcripts of CgCaspase3 as well as the apoptosis index of hemocytes were also decreased. These results collectively suggest that CgGLS-1 is the enzyme to synthesize Glu in oyster, which can modulate anti-bacterial immunity by regulating the secretion of pro-inflammatory cytokines CgIL17-5 and CgTNF-1, as well as hemocyte apoptosis.